The Attractor Mechanism Proceedings of the INFN-Laboratori Nazionali di Frascati School 2007 - Bellucci, Stefano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book is based upon lectures presented in June 2007 at the INFN-Laboratori Nazionali di Frascati School on Attractor Mechanism, directed by Stefano Bellucci. The symposium included such prestigious lecturers as S. Ferrara, M. Günaydin, P. Levay, and T. Mohaupt. All lectures were given at a pedagogical, introductory level, which is reflected in the specific "flavor" of this volume. The book also benefits from extensive discussions about, and related reworking of, the various contributions. In addition, this volume contains contributions originating from short presentations of recent original results and an essay on the relation between complexity science and high-energy physics by A. Zichichi. It is the fourth volume in a series of books on the general topics of supersymmetry, supergravity, black holes and the attractor mechanism.
SAM Lectures on Extremal Black Holes in d = 4 Extended Supergravity -- Lectures on Spectrum Generating Symmetries and U-Duality in Supergravity, Extremal Black Holes, Quantum Attractors and Harmonic Superspace -- Attractors, Black Holes and Multiqubit Entanglement -- From Special Geometry to Black Hole Partition Functions -- Complexity at the Fundamental Level -- Non-supersymmetric Attractors in Symmetric Coset Spaces -- Higher-Order String Effective Actions and Off-Shell d = 4 Supergravity.
Keywords: Physics; Quantum theory; Physics; Elementary Particles, Quantum Field Theory; Classical and Quantum Gravitation, Relativity Theory